The Use of Corrective Feedback to Improve English Speaking and Writing Achievements of The Eleventh Graders of Man 3 Palembang - Manggarsari, Yuniarsih (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aimed at investigating (1) whether or not there was significant differences in writing and speaking achievements between the students who were given the corrective feedback and those who were not, (2) how much speaking and writing aspects contributed to the students’ English writing and English speaking achievements, (3) the students’ perception on the use of corrective feedback in learning writing and speaking. Quasi-experimental design was used in this study. There were two groups in this study, experimental and control groups. Both groups consisted of thirty four students. English writing and English speaking pretest and posttest were given to both groups, but only experimental group was given the treatment. The data obtained were analyzed by using pair sample t-test, independent t-test, stepwise regression analyses, and percentage analysis to analyze the questionnaires. The result of independent sample t-test showed that there was significance difference in writing posttest (p<0.05) but the writing aspects such as grammar and mechanics had no significant difference (p>0.05). Meanwhile, the result of independent sample t-test of speaking posttest showed that there was significant difference (p<0.05). Based on the result of stepwise regression, grammar contributed 59.1% for student writing achievement. In speaking, corrective feedback contributed 739% to the students’ fluency. Based on the result of questionnaire, the students’ had positive perception towards the corrective feedback.